Pemanfaatan Minyak Jelantah sebagai Bahan Dasar Pembuatan Sabun Ramah Lingkungan dengan Penambahan Essential Oil di Desa Pasar Rawa - Sabrina Aisha Putri Lubis; Apriani Syahputri; Roslina Sahara; Rasyid Ridho Siregar; Dwi Ardy Dermawan (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
Cooking oil is a staple food widely used in daily cooking. However, repeated use of cooking oil, resulting in its conversion into used cooking oil, can have negative impacts on both health and the environment. Used cooking oil that has changed color and quality is carcinogenic and has the potential to increase the risk of cardiovascular disease if consumed again. Furthermore, improper disposal of used cooking oil can cause environmental pollution because it is difficult to decompose. This study aims to examine the wise management of household waste, especially used cooking oil, by utilizing it into products with utility value. One form of utilization is processing used cooking oil into environmentally friendly soap for laundry purposes. This activity was carried out as a form of community service through training in making soap from used cooking oil with the addition of essential oils for aromatherapy for residents of Pasar Rawa Village, Gebang District, Langkat Regency. The research method used was qualitative, with observation and direct participation in the training activities. The results showed that participants, particularly housewives, demonstrated high enthusiasm and were actively involved in both the presentation and the soap-making practices. This activity not only raised public awareness of the importance of managing used cooking oil waste but also provided new skills that have the potential to support family economic growth.